2000
DOI: 10.1074/jbc.m003701200
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein 90 Antagonist Novobiocin Interacts with a Previously Unrecognized ATP-binding Domain in the Carboxyl Terminus of the Chaperone

Abstract: Heat shock protein 90 (Hsp90), one of the most abundant chaperones in eukaryotes, participates in folding and stabilization of signal-transducing molecules including steroid hormone receptors and protein kinases. The amino terminus of Hsp90 contains a non-conventional nucleotide-binding site, related to the ATP-binding motif of bacterial DNA gyrase. The anti-tumor agents geldanamycin and radicicol bind specifically at this site and induce destabilization of Hsp90-dependent client proteins. We recently demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
447
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(479 citation statements)
references
References 35 publications
(52 reference statements)
21
447
0
4
Order By: Relevance
“…c-Phosphate-linked ATP-Sepharose binding has been used as the first biochemical assay for the unambiguous identification of Hsp90 as an ATP-binding protein by Grenert et al [9]. Though C-terminal fragments of Hsp90 also bound to the resin [19], and we demonstrated that Hsp90 was able to bind in the presence of a saturating concentration of the N-terminal inhibitor, GA [20], others could not detect binding under these circumstances [29]. We were intrigued by this apparent contradiction, and made an additional attempt to resolve the discrepancy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…c-Phosphate-linked ATP-Sepharose binding has been used as the first biochemical assay for the unambiguous identification of Hsp90 as an ATP-binding protein by Grenert et al [9]. Though C-terminal fragments of Hsp90 also bound to the resin [19], and we demonstrated that Hsp90 was able to bind in the presence of a saturating concentration of the N-terminal inhibitor, GA [20], others could not detect binding under these circumstances [29]. We were intrigued by this apparent contradiction, and made an additional attempt to resolve the discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…Recent communications have reported a second ATPbinding site in the C-terminal domain of Hsp90 [19][20][21]. Our studies demonstrated that the C-terminal nucleotide binding site becomes accessible only after the occupancy of the N-terminal site and is sensitive to cisplatin [20].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Novobiocin is a small molecule inhibitor that binds to the CTD of Hsp90 (Marcu et al, 2000a;Marcu et al, 2000b;Soti et al, 2002). Like GA and radicicol, novobiocin inhibits the formation of Hsp90 complexes with client or p23, but unlike GA it also reduces the affinity of Hsp90 for TPR-containing co-chaperones that bind to the CTD (Allan et al, 2006;Yun et al, 2004).…”
Section: Small Molecules Also Shift the Conformation Of Hsp90mentioning
confidence: 99%